The Relationship Between Family Interaction and the Social-Emotional Development of 4-5 Year Old Children in Jorong Rajo Dani, Tanah Datar Regency - Khairiyah, Annisa; Setiawati, Setiawati (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2025)
This research is motivated by the low socio-emotional development in children aged 4-5 years. The family plays a crucial role in this process, especially through interactions between children and parents. The purpose of this study is to analyze interactions within the family and to analyze the socio-emotional development of children aged 4-5 years in Jorong Rajo Dani, Tanah Datar Regency. In addition, to identify the relationship between interactions within the family and the socio- emotional development of children aged 4-5 years in Jorong Rajo Dani, Tanah Datar Regency. This study uses a quantitative approach with a correlational design. The population that became the object of the study was 40 people. The sample was taken through a simple random sampling technique, resulting in 30 samples. The instrument used was a questionnaire, and data analysis used the product moment correlation formula and percentage formula. The findings of this study indicate a significant relationship between interactions within the family and the socio-emotional development of children aged 4-5 years in Jorong Rajo Dani, Tanah Datar Regency.